Analisis Performa Jaringan 5G NR Telkomsel Menggunakan Metode Single Site Verification (SSV) Kecamatan Kosambi, Kabupaten Tangerang - Fachrurriadi, Andhika; Yulindon Yulindon (Kampus Akademik Publiser, 2026)
Telkomsel has implemented 5G New Radio (NR) technology across various regions in Indonesia, including Kosambi District, Tangerang Regency, where one of its sites newly activated 5G NR service in late 2025. Following the activation, performance analysis is necessary to ensure the network operates in accordance with the Key Performance Indicators (KPI) established by the operator. This study aims to analyze the downlink performance of the Telkomsel 5G NR network in Kosambi District using the Single Site Verification (SSV) method through drive test. The parameters analyzed include RF Mode, Reference Signal Received Power (RSRP), Signal to Interference plus Noise Ratio (SINR), and Downlink Throughput. Measurement results obtained 813 sample points, where 796 points (97.909%) performed serving on the 5G NR network and 17 points (2.09%) on LTE. RSRP and SINR parameters achieved averages of -78.61 dBm and 12.45 dB respectively, while downlink throughput reached an average of 71.02 Mbps. This study illustrates the empiricaperformance of the Telkomsel 5G NR network in Kosambi District against the established KPI standards, providing an initial overview of network conditions following activation that can serve as a reference for further network evaluation.